2020
DOI: 10.1183/13993003.02108-2020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and COPD

Abstract: ERSpublications COPD patients have increased risk of severe pneumonia and poor outcomes when they develop COVID-19. This may be related to poor underlying lung reserves or increased expression of ACE-2 receptor in small airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
222
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(289 citation statements)
references
References 104 publications
14
222
1
12
Order By: Relevance
“…To verify whether TRIB3 expression is also decreased in the lungs of patients with comorbidities at high risk of developing severe COVID-19 such as asthma [ 27 ] and chronic obstructive pulmonary disease (COPD) [ 28 ], data of available studies were downloaded from public Gene Expression Omnibus (GEO) datasets (GSE158752, GSE85567 and GSE57148). Differential gene expression analysis was performed using the BioJupies platform by comparing each group of patients with asthma or COPD with their respective control group: 98 COPD vs. 91 controls, 57 Asthma vs. 28 controls, and 50 asthma vs. 17 controls.…”
Section: Methodsmentioning
confidence: 99%
“…To verify whether TRIB3 expression is also decreased in the lungs of patients with comorbidities at high risk of developing severe COVID-19 such as asthma [ 27 ] and chronic obstructive pulmonary disease (COPD) [ 28 ], data of available studies were downloaded from public Gene Expression Omnibus (GEO) datasets (GSE158752, GSE85567 and GSE57148). Differential gene expression analysis was performed using the BioJupies platform by comparing each group of patients with asthma or COPD with their respective control group: 98 COPD vs. 91 controls, 57 Asthma vs. 28 controls, and 50 asthma vs. 17 controls.…”
Section: Methodsmentioning
confidence: 99%
“…COPD (Chronic obstructive pulmonary disease) patients are very much susceptible to severe pneumonia upon infection with SARS-CoV-2 owing to enhanced expression of ACE2 receptor in the respiratory airways. The common respiratory medications given to COPD patients include inhaled and systemic corticosteroids, long-acting β 2 -agonists, and muscarinic antagonists [ 81 ]. But whether these medications mitigates or exacerbates COVID-19 infections remains obscure till date.…”
Section: Comorbidity Treatment Regimes For Covid-19 Patientsmentioning
confidence: 99%
“…Indeed, through high-sensitivity RNA in situ mapping technology, it has been shown that the highest ACE2 expression is detecting in the nose with a decreased expression all through the lower respiratory tract, this observation is paralleled by an outstanding gradient of SARS-CoV-2 infection in proximal (high) versus distal (low) pulmonary epithelial cultures [ 42 ]. Current smoking is associated with increased expression of gene for ACE2, and TMPRSS2 [ 43 , 44 , 45 , 46 ]. It has been shown that airway epithelial cell expression of CHRNA7, encoding α7-nAChR, is significantly correlated with the expression of ACE2 with a trend towards higher expression in current smokers as compared with former and never smokers [ 36 ].…”
Section: Introductionmentioning
confidence: 99%